Leadership Approach to Distribute Employee Workload in The Office of The Ministry of Religious Affairs - Imas Maesaroh; Dalilah Ayu Permatasari; Nur Kholis (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam Syarifuddin Lumajang, 2022)
Leadership must ensure all employees have equal tasks and responsibilities. This study aimed to explore (1) the workload of employees in the MoRA office and (2) the strategies leaders take to overcome employee work overload. This study employed three methods of data collection: observation, interviews, and documentation. The informants include the Head Section and the staff working at the Ministry of Religious Affairs Office of Gresik Regency. Data were analyzed using the stages offered by Miles and Huberman, including data reduction, data presentation, and conclusion. The results show that the division’s staff workload was relatively heavy. The Head Section applied a leadership strategy to overcome work overload by offering work cooperation and mutual assistance among employees. In addition, leadership strategy was applied using an analysis of organizational structures, appropriate leadership styles, and the evaluation process. This study implies that reducing work overload is critical to maintaining employees’ ongoing health and strengthening work efficiency and effectiveness.